Mutation of cyclodextrin glycosyltransferase by domain swapping and site-directed mutagenesis - Kong, Wan Looi (2010)
Cyclodextrins are widely applied in various fields such as cosmetic, food, pharmaceuticals, agricultural, chemical, environmental and coatings. Cyclodextrin glycosyltransferase (CGTase, EC 2.4.19) is an industrial enzyme that produce mixture of a-, ß-, and ?- cyclodextrins from starch. There has been numerous studies on mutagenesis of CGTase. In this study, a mutant CGTase H43T/Y87F which was previously constructed was further mutated by domain swapping and site-directed mutagenesis. Domain swapping was done by overlapping extension PCR where the domain B of parent enzyme was replaced with similar domain from thermostable strains Pyrococcus furiosus and Thermococcus kodakaraensis KOD1. For site directed mutagenesis, single mutation and double mutation was done by megaprimer PCR where asparagine at location 28 was mutated to arginine (N28R) and asparagine at location 28 and 29 were mutated to arginine (N28R/N29R) respectively. In the starch plate analysis, mutants constructed by domain swapping showed no halo zone formation while mutants N28R and N28R/N29R mutants shown halo zone formation. For characterization, N28R utilized sago as best starch substrate on cyclodextrin production but showed a longer incubation time to reach maximum yield as compared to wild type H43T/Y87F. Mutant N28R exhibited an optimum temperature of 50°C while the wild type at 60°C. Addition of calcium ions increases the thermal stability of N28R. However, it was found that the relative activity of N28R decreased at a faster rate compared to parent H43T/Y87F. Mutation may cause disruption of ionic interaction around calcium binding site 1 where the calcium ion can not bind or bind loosely to the calcium binding site 1.